Komunikasi Fatis Bahasa Melayu Dialek Ambon Kabupaten Buru Selatan Kajian Sosiosemantik - Indrayani, Nanik (Universitas Batanghari Jambi, 2024)
South Buru Regency is a pemekaran district of Buru Regency on Buru Island, Maluku Province.This study aims to describe the linguistic phenomenon, namely